Impeding or Accelerating Assimilation? Immigration Enforcement and Its Impact on Naturalization Patterns - Catalina Amuedo-Dorantes; Mary J. Lopez (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2018)
Naturalization bestows economic benefits to immigrants, their families and communities through greater access to employment opportunities, higher earnings, and homeownership. It is the cornerstone of immigrant assimilation in the United States. Yet, less than 800,000 of the estimated 8.8 million legal permanent residents eligible to naturalize do so on a yearly basis. Using data from the 2008-2016 American Community Survey, we analyze how the expansion of interior U.S. immigration enforcement affects naturalization patterns. We find that the intensification of interior enforcement increases migrants' propensity to naturalize and accelerates their naturalization, possibly in response to increased uncertainty about future immigration policy. Yet, the impacts are highly heterogeneous. For eligible-to-naturalize immigrants living in mixed-status households - households with at least one unauthorized member, we find the opposite effects. Intensified enforcement makes them less likely to naturalize or to delay their status adjustment, possibly to avoid any contact with immigration officials. Understanding how immigration policy influences naturalization decisions is important given the benefits to naturalization and the potential to counter the adverse impacts of tougher enforcement on the 16 million individuals, many of them U.S. citizens, residing in mixed-status households.
Keywords: F22; J15; K37; 330; Immigration enforcement; Naturalization; United States